Emergence of mcr-9.1 in Extended-Spectrum-β-Lactamase-Producing Clinical Enterobacteriaceae in Pretoria, South Africa: Global Evolutionary Phylogenomics, Resistome, and Mobilome - John Osei Sekyere (American Society for Microbiology, 2020)
ABSTRACT Extended-spectrum-β-lactamase (ESBL)-producing Enterobacteriaceae are critical-priority pathogens that cause substantial fatalities. With the emergence of mobile mcr genes mediating resistance to colistin in Enterobacteriaceae, clinicians are now left with few therapeutic options. Eleven clinical Enterobacteriaceae strains with resistance to cephems and/or colistin were genomically analyzed to determine their resistomes, mobilomes, and evolutionary relationships to global strains. The global phylogenomics of mcr genes and mcr-9.1-bearing genomes were further analyzed. Ten isolates were ESBL positive. The isolates were multidrug resistant and phylogenetically related to global clones but distant from local strains. Multiple resistance genes, including blaCTX-M-15 blaTEM-1, and mcr-9.1, were found in single isolates; ISEc9, IS19, and Tn3 transposons bracketed blaCTX-M-15 and blaTEM-1. Common plasmid types included IncF, IncH, and ColRNAI. mcr-9 was of close sequence identity to mcr-3, mcr-5, mcr-7, mcr-8, and mcr-10. Genomes bearing mcr-9.1 clustered into six main phyletic groups (A to F), with those of this study belonging to clade B. Enterobacter species and Salmonella species are the main hosts of mcr-9.1 globally, although diverse promiscuous plasmids disseminate mcr-9.1 across different bacterial species. Emergence of mcr-9.1 in ESBL-producing Enterobacteriaceae in South Africa is worrying, due to the restricted therapeutic options. Intensive One Health molecular surveillance might discover other mcr alleles and inform infection management and antibiotic choices. IMPORTANCE Colistin is currently the last-resort antibiotic for difficult-to-treat bacterial infections. However, colistin resistance genes that can move from bacteria to bacteria have emerged, threatening the safe treatment of many bacterial infections. One of these genes, mcr-9.1, has emerged in South Africa in bacteria that are multidrug resistant, further limiting treatment options for clinicians. In this work, we show that this new gene is disseminating worldwide through Enterobacter and Salmonella species through multiple plasmids. This worrying observation requires urgent action to prevent further escalation of this gene in South Africa and Africa.